International Business Expansion Strategies: A Data-Driven Approach with IBM SPSS - Williams, Tane; Kallas, Evelin; Garcia, Emily; Fitzroy, Arabella; Sithole, Precious (APTISI Transactions on Management (ATM), 2024)
This paper presents a structural framework to enhance time management proficiency within dynamic work environments. The framework integrates prioritization techniques, task scheduling methods, delegation strategies, and technology utilization to optimize time allocation and productivity. The methodology involves the application of the Eisenhower Matrix, Pareto Principle, and time-blocking techniques, supported by case studies in diverse professional settings. Results indicate a 20% improvement in project completion times, a 25% reduction in project turnaround time, and a 30% increase in project visibility. These findings underscore the framework’s effectiveness in enhancing time management and achieving long-term success. Implications include recommendations for continuous refinement and integration of emerging technologies.